Sistem Navigasi pada Mobile Robot dengan Global Positioning System (GPS) - Ade Silvia Handayani (Annual Research Seminar (ARS), 2016)
This paper present the use of Global Positioning Systems (GPS) as navigational system for a ground based mobile robot. The proposed mobile robot contains a GPS system for navigation and sensors utrasonic for obstacle avoidance system. The Mobile robot navigates to the waypoint specified by the user through communication system xbee and avoids the obstacles in its way to destination. Mobile Robot can navigate through desired waypoint and at the same time apply the obstacle avoidance rules